Crime prevention, migration control and surveillance practices: welfare bureaucracy as mobility deterrent - Nagy, Veronika (Routledge, 2019)
Introduction -- Critical theories : social sorting and surveillance in a digital welfare labyrinth -- Roma, a global ethnic minority -- Welfare policy and the new social sorting of Europe -- Mediators, protectors and pathfinders : invisible players in Roma mobility approaches -- Accessing benefits abroad -- Commodification online : social security claims in virtual bureaucracies -- Conclusion -- References -- Appendices